Cattle farmer awareness and behavior regarding prevention of zoonotic disease transmission in Senegal - Tebug, Stanly Fon; Kamga-Waladjo, A.R.; Ema, P.J.N.; Muyeneza, C.; Kane, O.; Seck, A.; Ly, M.T.; Lo, M. (Informa UK Limited, 2015)
Livestock farmers are known to be at high risk of exposure to zoonosis. A convenience survey to assess Senegalese traditional cattle farmers’ knowledge and attitudes regarding zoonotic diseases with reference to bovine brucellosis was conducted. A total of 222 cattle farmers were interviewed. Just over a quarter (30.1%) of the study participants knew or had heard of zoonotic diseases, whereas 6.8% knew at least one mode of transmission. Rabies was the most named zoonotic disease by farmers who knew zoonosis. Meanwhile, no farmer had heard of bovine brucellosis. Identification of zoonotic disease varied significantly by farmer’s main activity. All farmers reported that they drink milk produced on their cattle farms, and 95.0% drank fresh milk without prior heat treatment. A majority of farmers (70.3%) regularly assist animals during parturition and abortion without protective gloves. Farmers were less likely to assist animals if they had attended formal education. This study reports low knowledge of zoonotic infections and low compliance to control practices. Investigations on possible zoonotic infections, tailored zoonotic disease control programs including disease awareness creation and improved farm management are strongly recommended.